Mitigation Of Loss Circulation Problems Using Calcium Carbonate In Well 'HF-05', 'Kanaan' Field - Heldy Febryanto; Firdaus; Risna; , Abdul Gafar Karim; Aprilino Alfa Kurmasela; Darmiyati, Iin; Annisa Efidiawati (AL-MIKRAJ Jurnal Studi Islam dan Humaniora, 2022)
Lossicirculation isione of theiproblems thatioften occursiin theidrillingiworld where loss of circulation or loss of circulation of mud is interpreted as a loss of circulation in a small amount or all of the drilling mud when it is circulated, so that when the drilling takes place, the circulated mud enters the drilling zone. penetrated formation. The "HF-05" well in the "KANAAN" fieldiis aidevelopmentiwell thatiaimsito proveithe existenceiof oil and gas reserves in Sukra District, Indramayu Regency. The loss circulation problem that occurred in the "HF-05" well occurred at a depth of 1945 mMD, route with a total loss of 278 bbl with a mud weight of 1.19 sg. The methodology used in handling loss circulation is collecting the necessary data, calculating hydrostatic pressure (PH), calculating drilling hydraulics, and identifying the causes of loss circulation by comparing hydrostatik pressure (PH) with formation pressure. Then carry out countermeasures using loss circulation material (LCM) type Calcium Carbonat. The results of countermeasures for loss circulation using loss circulation material (LCM) type Calcium Carboante in the "HF-05" well were successful with hydrostatik pressure (PH) lower than formation pressure (PF).